Effectiveness of Biopolymer-Bentonite Clay Composites in Wastewater Treatment - Mupasi, N.M.; Dube, D.; Chiririwa, H.; Naidoo, E.B. (Asian Journal of Chemistry, 2017)
The feasibility of employing wood-bentonite clay composite material as a low-cost and effective adsorbent for removal of cations from wastewater has been investigated. The wood-bentonite clay composites were prepared by a solution intercalation method. Results showed that the percentage adsorption of Pb2+, Mg2+ and Ca2+ from the effluent water was 88.46, 81.12 and 95.76 % respectively, using 10 g/L of the adsorbent. The desorbed wood-bentonite clay composites could be reused for adsorption of the cations.